The future of technology in conservation - Mulero-Pázmány, Margarita Cristina (Oxford University Press, 2021)
This final chapter discusses how conservation technology might evolve in the near future. The first section provides a global overview of the current scope of conservation technology. The second section focusses on the current limitations of conservation technology and describes advances that may help overcoming these constraints. I then discuss technological trends such as robotics and virtual reality, that are not widely used in conservation yet but offer promise to address current conservation challenges. I follow that with examples of integrating different technologies - with and without human intervention- in conservation research and management. Finally, I will touch on the barriers to integrating technology into conservation and propose solutions to overcome them.
Keywords: Fauna - Protección - Innovaciones tecnológicas; Conservation technology,; Drones; Camera traps